2020
DOI: 10.7150/thno.45016
|View full text |Cite
|
Sign up to set email alerts
|

CT Scans of Patients with 2019 Novel Coronavirus (COVID-19) Pneumonia

Abstract: Rationale:The increasing speed of confirmed 2019 novel coronavirus (COVID-19) cases is striking in China. The purpose of this study is to summarize the outcomes of patients with novel COVID-19 pneumonia (NCP) at our institution. Methods: In this single-center study, we retrospectively included 118 cases of NCP, from January 16, 2020 to February 4, 2020. The clinical outcomes were monitored up to February 11, 2020. The outcomes of NCP patients were phase summarized at our institution. Three kinds of responses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
98
1
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(109 citation statements)
references
References 13 publications
5
98
1
5
Order By: Relevance
“…Fourth, temporal changes on chest CT imaging during the course of disease could not be assessed. Although several of the studies that were included also reported some information on temporal changes on chest CT images during the course of disease, 15,22,27,28,32,[34][35][36][37][38]40 they had from a considerable amount of flaws and limitations in the analysis of temporal changes on chest CT images. None of these studies described sufficient details of the patients who underwent chest CT imaging at different time points to understand potentially confounding factors on the temporal course of chest CT imaging findings (such as pulmonary comorbidities and therapies that were administered).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Fourth, temporal changes on chest CT imaging during the course of disease could not be assessed. Although several of the studies that were included also reported some information on temporal changes on chest CT images during the course of disease, 15,22,27,28,32,[34][35][36][37][38]40 they had from a considerable amount of flaws and limitations in the analysis of temporal changes on chest CT images. None of these studies described sufficient details of the patients who underwent chest CT imaging at different time points to understand potentially confounding factors on the temporal course of chest CT imaging findings (such as pulmonary comorbidities and therapies that were administered).…”
Section: Discussionmentioning
confidence: 99%
“…Time points of chest CT imaging during the course of disease were dissimilar among all studies, and all studies provided mere descriptive data without performing comprehensive statistical analyses to assess for differences in chest CT imaging findings between different time points. 15,22,27,28,32,[34][35][36][37][38]40 Furthermore, one study compared different patients who underwent chest CT imaging at different time points rather than evaluating the time course of chest CT imaging findings in the same patients. 15 In the other studies that did perform an intrapatient evaluation during the course of disease, either only a subset of patients underwent followup chest CT imaging, which caused selection bias, 22,27,28,32,[34][35][36][37][38] or chest CT imaging findings were insufficiently reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations